A Comparative Analysis of Stand-up Comedy in Contemporary China and A Collection of Classic Chinese Jokes - Wang, Aiqing (Lingual Journal of Language and Culture; Vol 17 No 1 (2024): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2024.v17.i01.p05, 2024)
Notwithstanding the fact that ?? youmo ‘humour’ is a neologism and transliteration coined in the 1920s, the conception has been existing in Chinese civilisation for millennia. The earliest extant treatise on humour in Chinese literature is regarded to be an anthology ?? Xiao Lin ‘The Forest of Laughs’ cumulated circa 2 nd c CE, yet the most illustrious pre-modern jestbook is a 1791 assemblage entitled ???? Xiao Lin Guang Ji ‘A Collection of Classic Chinese Jokes’. In the 2000s, stand-up comedy entered China’s entertainment market as a niche cultural import, though it was, and still is, mistranslated into ??? tuokouxiu ‘talk show’. Recently, stand-up comedy attains visibility in China by means of phenomenal online programmes. I postulate that Chinese stand-up comedy is featured by unique attributes, in that it is disparate from ‘A Collection of Classic Chinese Jokes’ and the traditional theatrical comedy called ?? xiangsheng ‘cross-talk’, and it is not parallel to its equivalent in the West either. To be more specific, being subject to stringent censorship, stand-up comedy in China is circumspect about content appertaining to (homo)sexual titillation and supernaturalism. Nonetheless, I posit that in terms of inducing humorous effects, contemporary stand-up comedy still evinces similitude to ‘A Collection of Classic Chinese Jokes’ from phonetic, semantic and pragmatic perspectives.